The cytochrome bc1 complex as an antipathogenic target. Issue 18 (9th July 2020) - Fisher, Nicholas; Meunier, Brigitte; Biagini, Giancarlo A.
Abstract : The cytochrome bc 1 complex is a key component of the mitochondrial respiratory chains of many eukaryotic microorganisms that are pathogenic for plants or humans, such as fungi responsible for crop diseases and Plasmodium falciparum, which causes human malaria. Cytochrome bc 1 is an enzyme that contains two (ubi)quinone/quinol‐binding sites, which can be exploited for the development of fungicidal and chemotherapeutic agents. Here, we review recent progress in determination of the structure and mechanism of action of cytochrome bc 1, and the associated development of antimicrobial agents (and associated resistance mechanisms) targeting its activity. Abstract :